Burden of Obstetrics and Gynaecological Referrals to Tertiary Health Care System - Memon, Sarwat; Salman, Amna; Mumtaz, Afshan; Memon, Mehnaz (Journal of Gandhara Medical and Dental Science, 2023)
OBJECTIVES This study aimed to assess the burden of obstetrics and gynaecological cases, causes and pattern of referral to tertiary care hospital. METHODOLOGY This descriptive cross-sectional study was carried out from May 2022-July 2022 using the data of patients who were referred to the Department of Obstetrics and Gynecology Unit 2 at Isra University Hospital from various primary, secondary, tertiary, and private hospitals for any obstetric or gynaecological emergency were the primary source of data. The confidentiality of each patient was carefully respected. This study evaluated the prevalence, reasons and pattern of referral of various obstetric and gynaecological conditions for which patients were referred to Isra University Hospital within the study duration and the management options provided to these patients. RESULTS The gynaecological cases accounted for the majority (71%) of referrals. Patients between 21-30 yrs of age comprised 51% of the total. Most patients (20%) were multipara in their third trimester (18%). High-risk patients (60%) were this study’s most common reason for referral, whereas financial restrictions (4%) were the least common. Only 5% of patients were referred from other tertiary care facilities, whereas 49% of patients came from the primary sector (49%), secondary (33%), and private (13%). CONCLUSION There is an imperative need to upgrade health system infrastructure, mainly primary and secondary health care systems and especially in the field of maternal and childcare, to enable prompt and appropriate diagnosis and management of various conditions in all nearby hospitals.